Linkage of Credit on BI Rate, Funds Rate, Inflation and Government Spending on Capital - Sipahutar, Mangasa Augustinus; Oktaviani, Rina; Siregar, Hermanto; Juanda, Bambang (Universitas Negeri Semarang, 2017)
Linkage of credit on BI rate, funds rate, inflation, and government spending on capital provides evidence from Indonesia. This paper found advance explanation about banks credit as monetary transmission channel and its role on Indonesian economy. We used credit depth as a ratio of banks credit to GDP nominal, to explain the role of credit in Indonesian economy. We developed a VAR model to measure the response of credit to BI rate, funds rate and inflation rate, and OLS method to find out how banks credit response to government spending on capital. This paper revealed bi-direction causality between credit and BI rate, credit and funds rate, and credit and inflation. There is trade-off between credit and BI rate, credit and funds rate, and credit and inflation, but government spending on capital promotes credit depth. We found that Indonesian banking is bank view, allocated their credit based on their performance, not merely on the monetary policy determined by central bank. For bank view perspectives, we analyzed the link between LDR as an indicator of credit channel mechanism to NPLs and CAR. We found that there is no significant effect of CAR to LDR, but has a strong negatively relationship between NPLs to LDR. This evidence indicates that commercial banks in Indonesia allocated their credit do not related to their capital but merely to the quality of their credit portfolio.